Quantitative analysis of hyperkinetic seizures and correlation with seizure onset zone. (7th May 2020) - Fayerstein, Julie; McGonigal, Aileen; Pizzo, Francesca; Bonini, Francesca; Lagarde, Stanislas; Braquet, Aurore; Trébuchon, Agnès; Carron, Romain; Scavarda, Didier; Julia, Scholly; Lambert, Isabelle; Giusiano, Bernard; et al.
Abstract: Objective: Hyperkinetic epileptic seizures (HKS) are difficult to characterize and localize according to semiologic features. We propose a multicriteria scale to help visual analysis and report results of cerebral localization. Methods: We assessed seizures from 37 patients with HKS, explored with stereoelectroencephalography during presurgical evaluation. We used a multicriteria scale (hyperkinetic seizure scale [HSS]) with 10 semiologic features, scored independently by two neurologists. The item scores were used to group seizures using the k‐means method. Semiologic features were correlated with the seizure onset zone (SOZ) localization (temporal, prefrontal dorsolateral, prefrontal ventromesial, parietal, insular). Results: Fifty‐five seizures were analyzed, and each item of the HSS was compared between the two examiners with good interrater agreement (85.3%). Dystonia, integrated behavior, and bilateral or unilateral hyperkinetic movements were statistically significant according to localization. Three clusters were identified according to the HSS and correlated with different patterns of anatomic localization of SOZ. Cluster 1 was characterized clinically by asymmetric hyperkinetic movements associated with marked dystonia and vocalization. It mainly included parietal seizures. Cluster 2 was characterized by bilateral and symmetrical stereotyped hyperkinetic movements without dystonia. It represented half of temporal seizures and one‐third of prefrontal seizures (dorsolateral). Cluster 3 was characterized by seizures with strong emotionality and vocalization with bilateral and symmetrical hyperkinetic movements and integrated behavior. It involved half of temporal seizures and a majority of prefrontal (ventromesial) seizures. Significance: We propose a first attempt to quantify clinical patterns of HKS. The HSS may help to predict SOZ localization according to three main groups of hyperkinetic seizures.